Analysis of Opportunities and Threats in Indonesia's International Trade: A Case Study of Indonesian and Malaysian Plantation Commodities - Intan Mahrani J Gumohung (Takaza Innovatix Labs Ltd., 2026)
This study aims to explore the possibilities and risks faced by Indonesia's foreign trade sector, particularly in plantation commodities, with an emphasis on comparisons with Malaysia in the APEC context. The approach applied in this study is a literature study, which includes the collection of secondary data from various sources, including journals, official government reports, and international publications. The analysis findings indicate that Indonesia has significant capabilities in developing plantation commodities, such as palm oil, coffee, and rubber, thanks to its vast land area and favorable climate conditions. However, there are several challenges such as competition with Malaysia, environmental sustainability issues, and fluctuations in international trade policies that pose a threat to Indonesia's competitiveness in the global market. This study is expected to provide guidance for policymakers and industry players to formulate effective strategies to improve the competitiveness of Indonesia's plantation commodity trade in the international market